T-Cell Cytokine Gene Polymorphisms and Vitamin D Pathway Gene Polymorphisms in End-Stage Renal Disease due to Type 2 Diabetes Mellitus Nephropathy: Comparisons with Health Status and Other Main Causes of End-Stage Renal Disease - Alicja E. Grzegorzewska; Grzegorz Ostromecki; Paulina Zielińska; Adrianna Mostowska; Paweł P. Jagodziński (Journal of Diabetes Research)
Background. T-cell cytokine gene polymorphisms and vitamin D pathway gene polymorphisms were evaluated as possibly associated with end-stage renal disease (ESRD) resulting from type 2 diabetes mellitus (DM) nephropathy. Methods. Studies were conducted among hemodialysis (HD) patients with ESRD due to type 2 DM nephropathy, chronic glomerulonephritis, chronic infective tubulointerstitial nephritis, and hypertensive nephropathy as well as in healthy subjects. A frequency distribution of T-cell-related interleukin (IL) genes (IL18 rs360719, IL12A rs568408, IL12B rs3212227, IL4R rs1805015, IL13 rs20541, IL28B rs8099917, IL28B, and rs12979860) and vitamin D pathway genes (GC genes: rs2298849, rs7041, and rs1155563; VDR genes: rs2228570, rs1544410; and RXRA genes: rs10776909, rs10881578, and rs749759) was compared between groups. Results. No significant differences in a frequency distribution of tested polymorphisms were shown between type 2 DM nephropathy patients and controls. A difference was found in IL18 rs360719 polymorphic distribution between the former group and chronic infective tubulointerstitial nephritic patients (Ptrend=0.033), which also differed in this polymorphism from controls (Ptrend=0.005). Conclusion. T-cell cytokine and vitamin D pathway gene polymorphisms are not associated with ESRD due to type 2 DM nephropathy in Polish HD patients. IL18 rs360719 is probably associated with the pathogenesis of chronic infective tubulointerstitial nephritis.